2002
DOI: 10.1161/01.hyp.0000013734.33441.ea
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo klotho Gene Transfer Ameliorates Angiotensin II-Induced Renal Damage

Abstract: Abstract-The klotho gene, originally identified by insertional mutagenesis in mice, suppresses the expression of multiple aging-associated phenotypes. This gene is predominantly expressed in the kidney. Recent studies have shown that expression of renal klotho gene is regulated in animal models of metabolic diseases and in humans with chronic renal failure. However, little is known about the mechanisms and the physiological relevance of the regulation of the expression of the klotho gene in the kidney in some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
191
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(200 citation statements)
references
References 20 publications
5
191
1
3
Order By: Relevance
“…Klotho overexpression lessens progression of CKD, improves Pi metabolism, and protects the vasculature from calcification. Previous studies showed that overexpressing Klotho by viral-based gene transfer 34 or genetic manipulation 33 attenuated progressive renal injury, but the Klotho status and systemic complications of CKD were not studied. Because Klotho is present in multiple body fluids, 25,27,36,57 the restoration of Klotho clearly exerts multiple systemic effects in addition to renoprotection.…”
Section: Pathogenic Role Of Klotho In Progression Of Ckd and Its Compmentioning
confidence: 99%
See 1 more Smart Citation
“…Klotho overexpression lessens progression of CKD, improves Pi metabolism, and protects the vasculature from calcification. Previous studies showed that overexpressing Klotho by viral-based gene transfer 34 or genetic manipulation 33 attenuated progressive renal injury, but the Klotho status and systemic complications of CKD were not studied. Because Klotho is present in multiple body fluids, 25,27,36,57 the restoration of Klotho clearly exerts multiple systemic effects in addition to renoprotection.…”
Section: Pathogenic Role Of Klotho In Progression Of Ckd and Its Compmentioning
confidence: 99%
“…Renal Klotho mRNA is lower in a five-sixths nephrectomy model of CKD and in human nephrectomy samples from end-stage sclerotic kidneys. 30 -32 A modest amelioration of proteinuria and renal function was observed when Klotho was overexpressed genetically in a chronic glomerulonephritis model 33 or via viral delivery in a chronic angiotension II 34 and a spontaneous hypertension model. 35 We will test three hypotheses: (1) CKD is a state of Klotho deficiency; (2) low Klotho is an early marker of CKD; and (3) Klotho deficiency contributes to VC and Klotho replacement ameliorates CKD via multiple mechanisms.…”
mentioning
confidence: 99%
“…Of note, restoration of klotho by gene transfer improves angiotensin II-induced proteinuria. 70 As this discussion attests, the FGF-23/klotho system is strongly connected with the RAAS (Fig 1). Abnormal activation of the systemic and local RAAS is found commonly in patients with CKD and deeply influences medium-to long-term control of both blood pressure and proteinuria.…”
Section: Cross-talk Among the 3 "Ps" In The Pathogenesis Of Ckd Progrmentioning
confidence: 71%
“…87,88 Inflammation and oxidative stress are linked inseparably and represent major mediators of CKD progression and the associated cardiovascular complications. 62,70,81,89 …”
Section: Cross-talk Among the 3 "Ps" In The Pathogenesis Of Ckd Progrmentioning
confidence: 99%
“…There is no doubt that this system has a pivotal role in the development of DN. Previous research has shown that renal creatinine clearance increased and urinary protein excretion decreased after the Klotho gene was injected into the body of rats with continuous ATII infusion [15]. In conclusion, in diabetic nephropathy, the activation of RAAS inhibits the expression of the Klotho protein in the kidney and the Klotho gene can induce renal damage by inhibiting RAAS.…”
Section: Raasmentioning
confidence: 72%